Antimicrobial Peptides in Biomedical Device Manufacturing - Riool, Martijn; de Breij, Anna; Drijfhout, Jan W.; Nibbering, Peter H.; Zaat, Sebastian A. J. (Frontiers in Chemistry, 2017)
Over the past decades the use of medical devices, such as catheters, artificial heart valves, prosthetic joints and other implants, has grown significantly. Despite continuous improvements in device design, surgical procedures and wound care, biomaterial-associated infections (BAI) are still a major problem in modern medicine. Conventional antibiotic treatment often fails due to the low levels of antibiotic at the site of infection. The presence of biofilms on the biomaterial and/or the multidrug-resistant phenotype of the bacteria further impair the efficacy of antibiotic treatment. Removal of the biomaterial is then the last option to control the infection. Clearly, there is a pressing need for alternative strategies to prevent and treat BAI. Synthetic antimicrobial peptides (AMPs) are considered promising candidates as they are active against a broad spectrum of (antibiotic-resistant) planktonic bacteria and biofilms. Moreover, bacteria are less likely to develop resistance to these rapidly-acting peptides. In this review we highlight the four main strategies, three of which applying AMPs, in biomedical device manufacturing to prevent BAI. The first involves modification of the physicochemical characteristics of the surface of implants. Immobilization of AMPs on surfaces of medical devices with a variety of chemical techniques is essential in the second strategy. The main disadvantage of these two strategies relates to the limited antibacterial effect in the tissue surrounding the implant. This limitation is addressed by the third strategy that releases AMPs from a coating in a controlled fashion. Lastly, AMPs can be integrated in the design and manufacturing of additively manufactured / 3D-printed implants, owing to the physicochemical characteristics of the implant material and the versatile manufacturing technologies compatible with antimicrobials incorporation. These novel technologies utilizing AMPs will contribute to development of novel and safe antimicrobial medical devices, reducing complications and associated costs of device infection.